2009
DOI: 10.1677/joe-09-0021
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol inhibits 11β-hydroxysteroid dehydrogenase type 1 activity in rodent adipocytes

Abstract: 17b-Estradiol (E 2 ) serves as an anti-obesity steroid; however, the mechanism underlying this effect has not been fully clarified. The effect of E 2 on adipocytes opposes that of glucocorticoids, which potentiate adipogenesis and anabolic lipid metabolism. The key to the intracellular activation of glucocorticoid in adipocytes is 11b-hydroxysteroid dehydrogenase type 1 (11b-HSD1), which catalyses the production of active glucocorticoids (cortisol in humans and corticosterone in rodents) from inactive 11-keto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 76 publications
2
23
0
Order By: Relevance
“…In addition, these data showed that resveratrol does not inhibit G6PT, which is located in the membrane of the endoplasmic reticulum and supplies G6P to the lumen (Chou et al 2002). Further, these results were consistent with features of previous studies, indicating that no inhibition of H6PD by E 2 and 2-arylbenzofuran derivatives was observed (Tagawa et al 2009, Kiyonaga et al 2012. These characteristic properties might also be because of the typical structure of the spatial configuration of the two hydroxyl groups as observed in resveratrol, E 2 , or 2-arylbenzofuran derivatives.…”
Section: Figuresupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, these data showed that resveratrol does not inhibit G6PT, which is located in the membrane of the endoplasmic reticulum and supplies G6P to the lumen (Chou et al 2002). Further, these results were consistent with features of previous studies, indicating that no inhibition of H6PD by E 2 and 2-arylbenzofuran derivatives was observed (Tagawa et al 2009, Kiyonaga et al 2012. These characteristic properties might also be because of the typical structure of the spatial configuration of the two hydroxyl groups as observed in resveratrol, E 2 , or 2-arylbenzofuran derivatives.…”
Section: Figuresupporting
confidence: 92%
“…Culture and differentiation of 3T3-L1 cells and microsome preparation Differentiated 3T3-L1 adipocytes and intact microsomes from mesenteric fat pads and the liver and kidney of rats were prepared according to the method described elsewhere (Tagawa et al 2009). Because it has been reported that there is no isozyme for 11b-HSD1 in liver or adipose tissue from humans and rodents, we confirmed this in this study.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17) Measurement of 11β-HSD1 Activity 11β-HSD1 activity (11-oxoreductase) was measured using microsomes from rat mesenteric fat depots, or adipocytes from 3T3-L1 according to the method described previously. 16,18) Briefly, 15 µL microsomes (1.6 mg protein/mL) were added to MOPS buffer (100 mM KCl, 20 mM NaCl, 20 mM MOPS, pH 7.4) containing NADPH (1 mM) and 11-dehydrocorticosterone (1 µM) with and without various concentrations of the test compound and the reactants were incubated at 37°C for 40 min. After extraction with dichloromethane and evaporation in vacuo, corticosterone concentrations were measured by reversed-phase semi-micro HPLC in isocratic mode (water : methanol = 45 : 55, v/v%) with UV detection.…”
Section: Methodsmentioning
confidence: 99%